Semiconductor adhesive, semiconductor device, and method for manufacturing semiconductor device

CN116195052BActive Publication Date: 2026-10-20RESONAC CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202180062120.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-12-21
Filing Date
2021-09-13
Publication Date
2026-10-20
Estimated Expiration
2041-09-13

AI Technical Summary

Benefits of technology

[0030]根据本发明,在经由半导体用黏合剂将多个半导体芯片临时固定于被装载部件上,并一并进行固化和密封的工艺中,能够减少可能残留于半导体用黏合剂中的空隙。根据本发明,能够提供一种能够减少这种空隙,并且能够制作连接性优异的半导体装置的半导体用黏合剂、以及使用了该半导体用黏合剂的半导体装置及其制造方法。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116195052B_ABST
    Figure CN116195052B_ABST
Patent Text Reader

Abstract

The present application provides a semiconductor adhesive comprising a thermoplastic resin, a thermosetting resin, a curing agent, and an organic acid, wherein the organic acid is a compound having two or more acidic functional groups and an acid dissociation constant pKa of 4.0 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an adhesive for semiconductors, and a semiconductor device and a method for manufacturing the same. Background Technology

[0002] In the past, when connecting semiconductor chips to substrates, wire bonding methods using fine metal wires such as gold wires were widely used.

[0003] In recent years, in order to meet the requirements of high functionality, high integration, and high speed of semiconductor devices, conductive protrusions called bumps are formed on semiconductor chips or substrates, and the flip chip connection method (FC connection method) that directly connects semiconductor chips and substrates is becoming more and more popular.

[0004] For example, regarding the connection between semiconductor chips and substrates, the COB (Chip On Board) type connection widely used in BGA (Ball Grid Array) and CSP (Chip Size Package) also conforms to the FC connection method. Furthermore, the FC connection method is also widely used in COC (Chip On Chip) type connections where interconnects (bumps or wirings) are formed on the semiconductor chip to connect semiconductor chips, and in COW (Chip On Wafer) type connections where interconnects (bumps or wirings) are formed on the semiconductor wafer to connect semiconductor chips and semiconductor wafers (for example, see Patent Document 1).

[0005] Furthermore, with the strong demand for further miniaturization, thinning, and high-functionality packaging, chip stacking packages, POP (Package On Package), and TSV (Through-Silicon Via) formed by stacking and multi-leveling the aforementioned connection methods are becoming increasingly popular. This stacking and multi-level technology arranges semiconductor chips in three dimensions, thus reducing package size compared to two-dimensional methods. Moreover, because stacking and multi-level technology is effective in improving semiconductor performance, reducing interference, reducing mounting area, and saving power, it is attracting attention as a next-generation semiconductor wiring technology.

[0006] Previous technical documents

[0007] Patent documents

[0008] Patent Document 1: Japanese Patent Application Publication No. 2008-294382 Summary of the Invention

[0009] The technical problem to be solved by the invention

[0010] In recent years, from the perspective of improving productivity, a process has been proposed that involves temporarily fixing multiple semiconductor chips onto a mounting component (semiconductor chip, semiconductor wafer, wiring circuit board, etc.) using a semiconductor adhesive, followed by simultaneous or batch curing and sealing. In this process, the worktable is heated to a flowable level (approximately 60 to 155°C), and after temporarily fixing the semiconductor chips onto the mounting component, reflow or formal bonding is performed at a temperature above the melting point of the connection (e.g., approximately 260°C), thereby curing the semiconductor adhesive simultaneously or in batches. This process allows for the efficient fabrication of multiple semiconductor packages.

[0011] In the above process, since semiconductor chips are loaded sequentially, stage-based thermal stress is continuously applied to the initially loaded semiconductor chips and the semiconductor adhesive until the final semiconductor chip is loaded. Therefore, there is a tendency that if the number of semiconductor chips increases, the curing of the semiconductor adhesive temporarily fixing the initially loaded semiconductor chips will occur locally, and gaps will not be removed by the pressure applied during simultaneous curing, leaving residue. To improve this problem, the semiconductor adhesive needs to have excellent thermal stress resistance, i.e., the ability to suppress the curing reaction based on the thermal stress during temporary fixing.

[0012] Therefore, the object of the present invention is to provide a semiconductor adhesive capable of reducing the reaction rate after thermal runaway. Furthermore, the object of the present invention is to provide a semiconductor device using the above-described semiconductor adhesive and a method for manufacturing the same.

[0013] means for solving technical problems

[0014] To achieve the above objectives, the present invention provides an adhesive for semiconductors comprising a thermoplastic resin, a thermosetting resin, a curing agent, and an organic acid, wherein the organic acid is a compound having two or more acidic functional groups and an acid dissociation constant pKa of 4.0 or less.

[0015] The aforementioned organic acid has two or more acidic functional groups and an acid dissociation constant pKa of 4.0 or less, thereby enabling it to form a robust salt with at least a portion of the curing agent. Furthermore, by forming a salt between the curing agent and the organic acid, the reaction between the curing agent and the thermosetting resin can be inhibited. Therefore, according to the semiconductor adhesive containing the aforementioned organic acid, the curing reaction between the curing agent and the thermosetting resin can be suppressed by the heat treatment during temporary fixation, and the reaction rate after heat treatment can be reduced. Additionally, during final pressing, by applying heat higher than the heat treatment temperature based on the worktable during temporary fixation, the salt-containing curing agent separates from the organic acid. Thus, a semiconductor device can be obtained in which the separated curing agent reacts with the thermosetting resin during final pressing, and the residual voids are suppressed.

[0016] The aforementioned acidic functional groups may contain at least one group selected from the group consisting of carboxyl, sulfonic acid, and phosphate groups. There are no particular limitations as long as the aforementioned acidic functional groups are capable of forming a salt with the basic functional groups contained in the aforementioned curing agent; the aforementioned organic acid may also contain a variety of acidic functional groups.

[0017] The equivalent ratio of the acidic functional groups contained in the organic acid to the basic functional groups contained in the curing agent can be 1.0 or more. With this equivalent ratio of 1.0 or more, the amount of curing agent that has not reacted with the organic acid is reduced before formal pressing, which can further reduce the reaction rate after heat treatment compared to when the equivalent ratio is less than 1.0.

[0018] The organic acids mentioned above may include compounds represented by the following general formulas (1-1), (1-2), or (1-3).

[0019]

[0020] In equations (1-1), (1-2), and (1-3), R 1 R represents an electron-withdrawing group. 2 R represents a hydrogen atom or an electron-withdrawing group. 3 Indicates a hydrogen atom or a monovalent organic group, X represents an oxygen atom or a sulfur atom, n 1 n represents an integer from 0 to 15. 2 and n 3 They represent n respectively 2 +n 3 The choice of integers greater than 1, where m represents 1 or 2, is an integer between 2 and 15. Additionally, there are multiple R values. 3 They can be the same as each other, or they can be different.

[0021] The melting point of the aforementioned organic acid can be between 50 and 250°C. Since this organic acid fully exhibits fluxing activity before the curing reaction of the thermosetting resin and the curing agent occurs, semiconductor devices with further improved connection reliability can be achieved based on the semiconductor adhesive containing this organic acid.

[0022] The aforementioned curing agents may include amine curing agents. These compounds exhibit superior curing properties through the curing reaction between thermosetting resins and the curing agent, further improving the reflow resistance of semiconductor devices.

[0023] The aforementioned curing agent may contain imidazole-based curing agents. Using such compounds can further improve the stability of adhesives for semiconductors.

[0024] The structure of the aforementioned imidazole curing agent can include a triazine ring. Using such a compound can further improve the stability of adhesives for semiconductors.

[0025] The present invention also provides a method for manufacturing a semiconductor device, wherein the semiconductor device is a semiconductor device formed by electrically connecting the connection portions of a semiconductor chip and a wiring circuit board to each other, or a semiconductor device formed by electrically connecting the connection portions of multiple semiconductor chips to each other. The method for manufacturing the semiconductor device includes a sealing step of heating the semiconductor adhesive of the present invention under normal pressure or a pressurized atmosphere to cure it, and sealing at least a portion of the connection portion with the cured semiconductor adhesive.

[0026] Regarding the above manufacturing method, before the sealing process, it may further include: a process of arranging multiple semiconductor chips on a worktable; and a temporary fixing process of heating the worktable to 60 to 155°C, and sequentially arranging other semiconductor chips on each of the multiple semiconductor chips arranged on the worktable using the semiconductor adhesive, to obtain a multiple laminated body formed by sequentially stacking the semiconductor chips, the semiconductor adhesive, and the other semiconductor chips.

[0027] Alternatively, the manufacturing method described above may further include, prior to the sealing process, a process of: placing a wiring circuit board or a semiconductor wafer on a worktable; and a temporary fixing process of heating the worktable to 60 to 155°C, and sequentially placing a plurality of semiconductor chips on the wiring circuit board or semiconductor wafer placed on the worktable using the semiconductor adhesive, thereby obtaining a laminate formed by sequentially stacking the wiring circuit board, the semiconductor adhesive, and the plurality of semiconductor chips, or a laminate formed by sequentially stacking the semiconductor wafer, the semiconductor adhesive, and the plurality of semiconductor chips.

[0028] The present invention also provides a semiconductor device, which is a semiconductor device formed by electrically connecting the connection portions of a semiconductor chip and a wiring circuit board to each other, or a semiconductor device formed by electrically connecting the connection portions of multiple semiconductor chips to each other, wherein at least a portion of the connection portions is sealed by a cured product of the semiconductor adhesive of the present invention, which is heated and cured under normal pressure or a pressurized atmosphere.

[0029] Invention Effects

[0030] According to the present invention, in the process of temporarily fixing multiple semiconductor chips to a mounted component via a semiconductor adhesive and then curing and sealing them together, voids that may remain in the semiconductor adhesive can be reduced. According to the present invention, a semiconductor adhesive capable of reducing such voids and producing a semiconductor device with excellent connectivity, a semiconductor device using the semiconductor adhesive, and a method for manufacturing the same are provided. Attached Figure Description

[0031] Figure 1 This is a schematic cross-sectional view illustrating one embodiment of a semiconductor device.

[0032] Figure 2 This is a schematic cross-sectional view illustrating one embodiment of a semiconductor device.

[0033] Figure 3 This is a schematic cross-sectional view illustrating one embodiment of a semiconductor device.

[0034] Figure 4 It is a circuit diagram of the semiconductor chip used in the connectivity evaluation. Detailed Implementation

[0035] Hereinafter, an embodiment of the present invention will be described in detail with reference to the accompanying drawings, as appropriate. Furthermore, in the drawings, the same or corresponding parts are labeled with the same symbols, and repeated descriptions are omitted. Also, unless otherwise specified, positional relationships such as up, down, left, and right are based on the positional relationships shown in the drawings. Moreover, the scale of the drawings is not limited to the scale shown.

[0036] The upper and lower limits of the numerical ranges described in this specification can be combined arbitrarily. The numerical values ​​described in the examples can also be used as the upper or lower limits of the numerical ranges. In this specification, "(meth)acrylic acid" refers to acrylic acid or its corresponding methacrylic acid.

[0037] <Semiconductor Adhesives and Their Manufacturing Methods>

[0038] The semiconductor adhesive of this embodiment contains a thermoplastic resin (hereinafter referred to as "component (a)" as appropriate), a thermosetting resin (hereinafter referred to as "component (b)" as appropriate), a curing agent (hereinafter referred to as "component (c)" as appropriate), and an organic acid (hereinafter referred to as "component (d)" as appropriate). The semiconductor adhesive of this embodiment may also contain a filler (hereinafter referred to as "component (e)" as appropriate).

[0039] The calorific value of the semiconductor adhesive obtained by differential scanning calorimetry (DSC) in this embodiment, measured at 60 to 155°C, is less than 20 J / g. The differential scanning calorimetry is performed as follows: the weight of the semiconductor adhesive sample is set to 10 mg, the measurement temperature range is set to 30 to 300°C, the heating rate is set to 10°C / min, and the semiconductor adhesive is heated in an air or nitrogen atmosphere. The calorific value is calculated by integrating the peak area.

[0040] Conventional semiconductor adhesives exhibit a heat peak in the 60-155°C temperature range of the DSC curve. It is presumed that the heat generated in this temperature range originates from the reaction between the thermosetting resin and organic acid in the semiconductor adhesive. Furthermore, it is speculated that if this reaction occurs, the semiconductor adhesive undergoes localized curing, reducing its fluidity. On the other hand, the temporary fixation of semiconductor chips using semiconductor adhesives is typically performed by heating the semiconductor adhesive to, for example, 60-155°C and allowing it to flow appropriately. Therefore, it is presumed that in processes where multiple semiconductor chips are mounted onto a mounting component (semiconductor chip, semiconductor wafer, wiring circuit board, etc.) and temporarily fixed using a semiconductor adhesive, followed by simultaneous curing and sealing under pressure, if conventional semiconductor adhesives are used, during the temporary fixation of the semiconductor chips, the thermosetting resin in the semiconductor adhesive reacts with the organic acid, resulting in localized curing of the semiconductor adhesive. Consequently, during simultaneous curing under pressure, the adhesive does not flow sufficiently. On the other hand, in the semiconductor adhesive of this embodiment, when the heat generation of the DSC curve from 60 to 155°C is less than 20 J / g, it is difficult to cure in the temperature range (e.g., 60 to 155°C) where the semiconductor chip is temporarily fixed. Therefore, by using a semiconductor adhesive that meets the above-mentioned heat generation conditions in the above process, it is possible to maintain sufficient fluidity of the semiconductor adhesive and reduce the generation of voids when temporarily fixing multiple semiconductor chips together. Moreover, as a result of reducing the generation of voids, it is expected that during the reflow process, even if heating is performed at a temperature above the melting point of the connection (e.g., 260°C), it is less likely that adverse conditions (such as peeling of the semiconductor adhesive or poor electrical connection of the connection) will occur. In other words, a semiconductor adhesive that meets the above-mentioned heat generation conditions tends to improve the reflow reliability (reflow resistance) in the manufacture of semiconductor devices.

[0041] From the viewpoint that the effects of the present invention are readily obtained, the calorific value of the DSC curve at 60 to 155°C is preferably 15 J / g or less, more preferably 10 J / g or less, and even more preferably 5 J / g or less. From the viewpoint that the effects of the present invention are readily obtained, the calorific value of the DSC curve at 60 to 155°C may also be 20% or less, 15% or less, or 10% or less of the calorific value at 60 to 280°C. From the viewpoint that the effects of the present invention are readily obtained, the calorific value of the DSC curve at 60 to 280°C may be 50 J / g or more, or 100 J / g or more, or 200 J / g or less, or 180 J / g or less, or 50 to 200 J / g, 100 to 200 J / g, or 100 to 180 J / g. From the viewpoint that the effects of the present invention are readily obtained, the DSC curve preferably does not have a calorific value peak with an initial temperature below 155°C.

[0042] The components of the semiconductor adhesive constituting this embodiment will be described below.

[0043] (a) Thermoplastic resin

[0044] As for component (a), there is no particular limitation, and examples include phenoxy resins, polyimide resins, polyamide resins, polycarbodiimide resins, cyanate ester resins, acrylic resins, polyester resins, polyethylene resins, polyethersulfone resins, polyetherimide resins, polyvinyl acetal resins, amine ester resins, and acrylic rubbers. Among these, from the viewpoint of excellent heat resistance and film-forming properties, phenoxy resins, polyimide resins, acrylic resins, acrylic rubbers, cyanate ester resins, and polycarbodiimide resins are preferred, and phenoxy resins, polyimide resins, and acrylic resins are more preferred. These components (a) can be used alone or as a mixture or copolymer of two or more.

[0045] Regarding the weight-average molecular weight (Mw) of component (a), it is preferably 10,000 or more, more preferably 40,000 or more, and even more preferably 60,000 or more. With this component (a), film-forming properties and the heat resistance of the adhesive can be further improved. Furthermore, if the weight-average molecular weight is 10,000 or more, it is easier to impart flexibility to the film-like semiconductor adhesive, thus easily obtaining superior processability. Furthermore, regarding the weight-average molecular weight of component (a), it is preferably 1,000,000 or less, more preferably 500,000 or less. With this component (a), since the film viscosity is reduced, the embedding of bumps becomes better, enabling further gapless mounting. From these viewpoints, regarding the weight-average molecular weight of component (a), it is preferably 10,000 to 1,000,000, more preferably 40,000 to 500,000, and even more preferably 60,000 to 500,000.

[0046] Furthermore, in this specification, the weight-average molecular weight mentioned above represents the weight-average molecular weight of polystyrene measured using GPC (Gel Permeation Chromatography). An example of the measurement conditions for the GPC method is shown below.

[0047] Apparatus: HCl-8320GPC, UV-8320 (product name, manufactured by TOSOH CORPORATION) or HPLC-8020 (product name, manufactured by TOSOH CORPORATION)

[0048] Column: TSKgel superMultiporeHZ-M×2 or 2 pieces of GMHXL + 1 piece of G-2000XL

[0049] Detector: RI or UV detector

[0050] Column temperature: 25 to 40℃

[0051] Solution: Choose a solvent that dissolves the polymeric components. Examples of suitable solvents include THF (tetrahydrofuran), DMF (N,N-dimethylformamide), DMA (N,N-dimethylacetamide), NMP (N-methylpyrrolidone), and toluene. Alternatively, when choosing a polar solvent, the concentration of phosphoric acid can be adjusted to 0.05 to 0.1 mol / L (typically 0.06 mol / L), and the concentration of LiBr can be adjusted to 0.5 to 1.0 mol / L (typically 0.63 mol / L).

[0052] Flow rate: 0.30 to 1.5 mL / min

[0053] Standard material: polystyrene

[0054] Regarding the content of component (b) C b The content of component C relative to component (a) a The ratio of C b / C a (Mass ratio), preferably 0.01 or more, more preferably 0.1 or more, further preferably 1 or more, preferably 5 or less, more preferably 4.5 or less, and further preferably 4 or less. By adjusting the ratio C... b / C a Setting it to 0.01 or higher can result in better curing properties and adhesion. b / C a Setting it to below 5 yields better film-forming properties. From these perspectives, it is better than C. b / C a Preferably, it is 0.01 to 5, more preferably 0.1 to 4.5, and even more preferably 1 to 4.

[0055] Regarding the glass transition temperature of component (a), from the viewpoint of improving connection reliability, it is preferably -50°C or higher, more preferably -40°C or higher, and even more preferably -30°C or higher. From the viewpoint of lamination, it is preferably 220°C or lower, more preferably 200°C or lower, and even more preferably 180°C or lower. The glass transition temperature of component (a) is preferably -50 to 220°C, more preferably -40 to 200°C, and even more preferably -30 to 180°C. According to the semiconductor adhesive containing this component (a), wafer warpage can be further reduced during wafer-level mounting processes, and the heat resistance and film-forming properties of the semiconductor adhesive can be further improved. The glass transition temperature of component (a) can be measured using a differential scanning calorimeter (DSC).

[0056] Regarding the content of component (a), based on the total solid content of the semiconductor adhesive, it is preferably 30% by mass or less, more preferably 25% by mass or less, and even more preferably 20% by mass or less. If the content of component (a) is 30% by mass or less, the semiconductor adhesive exhibits good reliability during temperature cycling tests and maintains good adhesion even after moisture absorption at reflow temperatures around 260°C. Furthermore, regarding the content of component (a), based on the total solid content of the semiconductor adhesive, it is preferably 1% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more. If the content of component (a) is 1% by mass or more, the semiconductor adhesive can further reduce wafer warpage during wafer-level mounting processes and further improve the heat resistance and film-forming properties of the semiconductor adhesive. Furthermore, if the content of component (a) is 5% by mass or more, the generation of burrs and gaps during wafer shaping can be suppressed. Regarding the content of component (a), from the above-mentioned viewpoint and from the viewpoint that it is easy to impart flexibility to the film-like semiconductor adhesive and to obtain better processability, based on the total amount of solid components of the semiconductor adhesive, it is preferably 1 to 30% by mass, more preferably 3 to 30% by mass, and even more preferably 5 to 30% by mass. Furthermore, "total amount of solid components of the semiconductor adhesive" refers to the amount obtained by subtracting the amount of solvent contained in the semiconductor adhesive from the total amount of the semiconductor adhesive. In this specification, "total amount of solid components of the semiconductor adhesive" may also be referred to as "the total amount of components (a) to (e)".

[0057] (b) Thermosetting resins

[0058] As component (b), any component having two or more reactive groups within its molecule can be used without particular restrictions. Semiconductor adhesives contain thermosetting resins, which allow the adhesive to be cured by heating. The cured adhesive exhibits high heat resistance and strong adhesion to the chip, resulting in excellent resistance to reflow soldering.

[0059] Examples of components (b) include epoxy resins, phenolic resins, imide resins, urea resins, melamine resins, silicone resins, (meth)propylene oxides, and vinyl compounds. From the viewpoint of excellent heat resistance (resistance to reflow) and storage stability, epoxy resins, phenolic resins, and imide resins are preferred, more preferably epoxy resins and imide resins, and even more preferably epoxy resins. These components (b) can be used alone or as a mixture or copolymer of two or more. In conventional semiconductor adhesives, especially when the thermosetting resin is epoxy resin, melamine resin, or urea resin, it is easy to react with the organic acids described later in the temperature range of 60 to 155°C, tending to undergo localized curing before simultaneous curing. However, in this embodiment, even when the thermosetting resin contains at least one resin selected from the group consisting of epoxy resin, melamine resin, and urea resin, such reaction and localized curing are less likely to occur.

[0060] As epoxy resins and imide resins, for example, bisphenol A type epoxy resin, bisphenol F type epoxy resin, naphthalene type epoxy resin, phenolic varnish type epoxy resin, cresol phenolic varnish type epoxy resin, phenolic alkyl type epoxy resin, biphenyl type epoxy resin, triphenylmethane type epoxy resin, dicyclopentadiene type epoxy resin, and various multifunctional epoxy resins, nadimide resin, allyl nadimide resin, maleimide resin, amide imide resin, imide acrylate resin, various multifunctional imide resins, and various polyimide resins can be used. These can be used alone or as a mixture of two or more.

[0061] Regarding component (b), from the viewpoint of suppressing the decomposition and generation of volatile components during bonding at high temperatures, when the bonding temperature is 250°C, it is preferable to use a component with a heat weight reduction rate of 5% or less at 250°C, and when the bonding temperature is 300°C, it is preferable to use a component with a heat weight reduction rate of 5% or less at 300°C.

[0062] Regarding the content of component (b), based on the total solid content of the semiconductor adhesive, it is, for example, 5% by mass or more, preferably 15% by mass or more, and more preferably 30% by mass or more. Regarding the content of component (b), based on the total solid content of the semiconductor adhesive, it is, for example, 80% by mass or less, preferably 70% by mass or less, and more preferably 60% by mass or less. Regarding the content of component (b), based on the total solid content of the semiconductor adhesive, it is, for example, 5 to 80% by mass, preferably 15 to 70% by mass, and more preferably 30 to 60% by mass.

[0063] (c) Curing agent

[0064] (c) can be a curing agent capable of forming salts with the organic acids described later. Examples of (c) include amine curing agents (amines) and imidazole curing agents (imidazoles). When (c) contains an amine curing agent or an imidazole curing agent, it exhibits flux activity that inhibits the formation of an oxide film at the joint, thereby improving joint reliability and insulation reliability. Furthermore, when (c) contains an amine curing agent or an imidazole curing agent, storage stability is further improved, and it is less prone to decomposition or deterioration due to moisture absorption. Moreover, when (c) contains an amine curing agent or an imidazole curing agent, the curing speed is easily adjusted, and through rapid curing, short-time joints for the purpose of improving productivity can be easily achieved.

[0065] The following is an explanation of each curing agent.

[0066] (i) Amine curing agents

[0067] Dicyandiamine can be used as an amine curing agent, for example.

[0068] Regarding the content of the amine curing agent, it is preferably 0.1 parts by mass or more relative to 100 parts by mass of component (b) above. Furthermore, regarding the content of the amine curing agent, it is preferably 10 parts by mass or less relative to 100 parts by mass of component (b) above, more preferably 5 parts by mass or less. If the content of the amine curing agent is 0.1 parts by mass or more, there is a tendency for improved curability; if it is 10 parts by mass or less, there is a tendency for the semiconductor adhesive not to cure before forming the metal bond, making poor connection difficult to occur. From these viewpoints, regarding the content of the amine curing agent, it is preferably 0.1 to 10 parts by mass relative to 100 parts by mass of component (b), more preferably 0.1 to 5 parts by mass.

[0069] (ii) Imidazole curing agents

[0070] Examples of imidazole curing agents include 2-phenylimidazolium, 2-phenyl-4-methylimidazolium, 1-benzyl-2-methylimidazolium, 1-benzyl-2-phenylimidazolium, 1-cyanoethyl-2-undecaprin, 1-cyano-2-phenylimidazolium, 1-cyanoethyl-2-undecaprin, 1-cyanoethyl-2-undecaprin, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-triazine, and 2,4-diamino-6- [2'-Undecylimidazolyl-(1')]-ethyl-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-triazine isocyanate adduct, 2-phenylimidazolyl isocyanate adduct, 2-phenyl-4,5-dihydroxymethylimidazolium, 2-phenyl-4-methyl-5-hydroxymethylimidazolium and epoxy resin adducts with imidazoles. From the viewpoint of excellent curing properties, storage stability, and connection reliability, 1-cyanoethyl-2-undecylimidazole, 1-cyano-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole trimellitate, 1-cyanoethyl-2-phenylimidazole ontium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, and 2-phenyl-4-methyl-5-hydroxymethylimidazole are preferred. These can be used alone or in combination with two or more. Furthermore, they can also serve as potential curing agents for microencapsulation.

[0071] Regarding the content of the imidazole curing agent, it is preferably 0.1 parts by mass or more relative to 100 parts by mass of component (b). Furthermore, regarding the content of the imidazole curing agent, it is preferably 10 parts by mass or less relative to 100 parts by mass of component (b), more preferably 5 parts by mass or less, and even more preferably 2.3 parts by mass or less. If the content of the imidazole curing agent is 0.1 parts by mass or more, there is a tendency for improved curability. If the content of the imidazole curing agent is 10 parts by mass or less, the semiconductor adhesive will not cure before forming a metal bond, making poor connection less likely, and in a curing process under a pressurized atmosphere, the formation of voids is easily suppressed. From these viewpoints, regarding the content of the imidazole curing agent, it is preferably 0.1 to 10 parts by mass relative to 100 parts by mass of component (b), more preferably 0.1 to 5 parts by mass, and even more preferably 0.1 to 2.3 parts by mass.

[0072] (c) Components can be used alone or as a mixture of two or more. For example, imidazole curing agents can be used alone or together with amine curing agents. As component (c), curing agents other than those mentioned above that function as curing agents in component (b) can also be used.

[0073] Regarding the content of component (c), it is preferably 0.5 parts by mass or more relative to 100 parts by mass of component (b). Furthermore, regarding the content of component (c), it is preferably 20 parts by mass or less relative to 100 parts by mass of component (b), more preferably 6 parts by mass or less, and even more preferably 4 parts by mass or less. When the content of component (c) is 0.5 parts by mass or more, there is a tendency for sufficient curing. When the content of component (c) is 20 parts by mass or less, there is a tendency to suppress rapid curing leading to an increase in reaction sites, preventing shortening of molecular chains or residual unreacted groups that reduce reliability, and it is also easier to suppress residual voids during curing under a pressurized atmosphere. From these viewpoints, regarding the content of component (c), it is preferably 0.2 to 20 parts by mass relative to 100 parts by mass of component (b), more preferably 0.5 to 6 parts by mass, and even more preferably 0.5 to 4 parts by mass.

[0074] Regarding the content of component (c), based on the total solid content of the semiconductor adhesive, it is preferably 0.5% by mass or more. Furthermore, regarding the content of component (c), based on the total solid content of the semiconductor adhesive, it is preferably 2.3% by mass or less, more preferably 2.0% by mass or less, and even more preferably 1.5% by mass or less. When the content of component (c) is 0.5% by mass or more, there is a tendency for sufficient curing. When the content of component (c) is 2.3% by mass or less, there is a tendency to suppress rapid curing leading to an increase in reaction points, preventing shortening of molecular chains or residual unreacted groups that reduce reliability, and it is also easier to suppress residual voids during curing under a pressurized atmosphere. From these viewpoints, regarding the content of component (c), based on the total solid content of the semiconductor adhesive, it is preferably 0.5 to 2.3% by mass, more preferably 0.5 to 2.0% by mass, and even more preferably 0.5 to 1.5% by mass.

[0075] When the semiconductor adhesive contains an amine curing agent as component (c), it exhibits superior curing properties through a curing reaction with epoxy resin, thereby further improving the reflow resistance of the semiconductor device.

[0076] (d) Organic acids

[0077] (d) is an organic acid. By using an adhesive for semiconductors containing (d), the oxide film on the metal of the connection and the coating based on OSP treatment can be removed, thus easily obtaining excellent connection reliability.

[0078] Component (d) has two or more acidic functional groups. Furthermore, the acid dissociation constant pKa of component (d) is 4.0 or less. Because component (d) has two or more acidic functional groups and the acid dissociation constant pKa is 4.0 or less, the adhesive for semiconductors can reduce the post-thermal reaction rate based on the thermal history during temporary fixation.

[0079] Since component (d) has more than two acidic functional groups, it can also have multiple acid dissociation constants. An acid dissociation constant pKa of 4.0 or less means that at least one of the multiple acid dissociation constants has a value of 4.0 or less.

[0080] The acid dissociation constant pKa of component (d) is 4.0 or less, preferably 3.5 or less, and more preferably 2.5 or less. Furthermore, the acid dissociation constant pKa of component (d) is preferably 1.0 or more, more preferably 1.5 or more, and even more preferably 2.0 or more. By having the acid dissociation constant pKa of component (d) be 4.0 or less, it is possible to form a stronger salt with basic functional groups, thus suppressing the reaction with epoxy resin.

[0081] (d) Component, as an acidic functional group, may contain at least one group selected from the group consisting of carboxyl, sulfonic acid, and phosphoric acid groups. There is no particular limitation as long as the acidic functional group is capable of forming a salt with the basic functional group contained in the curing agent. By making (d) a compound containing a carboxyl group (e.g., a carboxylic acid), superior bonding reliability is readily obtained. Since (d) is a compound containing a carboxyl group (e.g., a carboxylic acid), from the viewpoint of readily obtaining the effects of the present invention, (b) is preferably at least one thermosetting resin selected from the group consisting of epoxy resin, amine ester resin, and urea resin, and (c) is preferably at least one curing agent selected from the group consisting of amine curing agents and imidazole curing agents. Furthermore, (d) may also contain a carboxyl group, a sulfonic acid group, or an acidic group other than a phosphoric acid group.

[0082] Regarding component (d), examples can be given of compounds having structures represented by the following general formulas (1-1), (1-2), or (1-3).

[0083]

[0084] In equations (1-1) to (1-3), R 1 R represents an electron-withdrawing group. 2 R represents a hydrogen atom or an electron-withdrawing group. 3 Indicates a hydrogen atom or a monovalent organic group, X represents an oxygen atom or a sulfur atom, n 1 n represents an integer from 0 to 15. 2 and n 3 They represent n respectively2 +n 3 The choice of integers greater than 1, ranging from 2 to 15, is used, where m represents 1 or 2. Additionally, there are multiple R... 3 They can be the same as each other, or they can be different.

[0085] Examples of electron-withdrawing groups include sulfonyl, nitro, cyano, halogen, and carbonyl groups. Component (d) may also have two or more electron-withdrawing groups. Furthermore, the α-carbon of the acidic functional group in component (d) may also constitute part of the electron-withdrawing group. For example, in formulas (1-2) above, the α-carbon of the acidic functional group becomes part of the carbonyl group. That is, component (d) can be said to have a structure in which an electron-withdrawing group is directly bonded to the α-carbon of the acidic functional group, or a structure in which the α-carbon of the acidic functional group constitutes part of the electron-withdrawing group. From the viewpoint of easily obtaining excellent flux activity and easily obtaining the effects of the present invention, the electron-withdrawing group preferably includes at least one selected from the group consisting of cyano, halogen, and carbonyl, and more preferably includes a carbonyl group.

[0086] (d) Component (d) is preferably a compound having 1 to 3 acidic functional groups, more preferably a compound having 1 to 3 carboxyl groups as acidic functional groups. Component (d) preferably includes at least one selected from the group consisting of monocarboxylic acids, dicarboxylic acids, and tricarboxylic acids. When using component (d) having 1 to 3 carboxyl groups, compared with using a compound having 4 or more carboxyl groups, it is possible to further suppress the viscosity increase of the semiconductor adhesive during storage, connection operations, etc., and to further improve the connection reliability of the semiconductor device.

[0087] (d) The component is more preferably a compound having two carboxyl groups (dicarboxylic acid). When it is a dicarboxylic acid, compared with a compound having one carboxyl group (monocarboxylic acid), it is less likely to volatilize even at high temperatures during connection, and the occurrence of voids can be further suppressed. Furthermore, if a compound having two carboxyl groups is used, compared with the use of a compound having three or more carboxyl groups, the viscosity increase of the semiconductor adhesive during storage, connection operations, etc., can be further suppressed, and the connection reliability of the semiconductor device can be further improved.

[0088] Regarding the melting point of component (d), it is preferably 50°C or higher, more preferably 60°C or higher, even more preferably 70°C or higher, preferably 250°C or lower, more preferably 150°C or lower, and even more preferably 130°C or lower. When the melting point of component (d) is 250°C or lower, the flux activity is readily and fully manifested before the thermosetting resin and curing agent undergo a curing reaction. Therefore, according to the semiconductor adhesive containing this component (d), when the chip is loaded, component (d) melts, and the oxide film on the solder surface is removed, thereby enabling a semiconductor device with further superior connection reliability. Furthermore, when the melting point of component (d) is 50°C or higher, the reaction is difficult to initiate at room temperature or on a high-temperature workbench, resulting in better storage stability. From these viewpoints, regarding the melting point of component (d), it is preferably 50 to 250°C, more preferably 60 to 150°C, and even more preferably 70 to 130°C.

[0089] (d) The melting point of the component can be measured using a general melting point measuring device. For the sample used to measure the melting point, it is necessary to reduce the temperature deviation within the sample by pulverizing it into a fine powder and using a small amount. Most samples are placed in a capillary tube closed at one end, but depending on the measuring device, there are also containers that sandwich the capillary tube between two microscope coverslips. Furthermore, if the temperature is raised rapidly, a temperature gradient will be generated between the sample and the thermometer, resulting in measurement error. Therefore, it is preferable to measure the melting point at a rate of heating less than 1°C per minute.

[0090] The sample for melting point measurement is prepared as a fine powder as described above. Therefore, due to irregular surface reflection, the sample is opaque before melting. Generally, the temperature at which the sample begins to become transparent is taken as the lower limit of the melting point, and the temperature at which it completely melts is taken as the upper limit. Various measuring devices exist, but the most classic device uses a capillary tube filled with the sample mounted on a two-tube thermometer and heated in a heat bath. To attach the capillary tube to the two-tube thermometer, a highly viscous liquid is used as the heat bath, often concentrated sulfuric acid or silicone oil, and the sample is installed near the reservoir at the front of the thermometer. Furthermore, as a melting point measuring device, it is also possible to use a metal heating block for heating, measuring transmittance, adjusting heating, and automatically determining the melting point.

[0091] In addition, in this specification, a melting point below 250°C means the upper limit of the melting point is below 250°C, and a melting point above 50°C means the lower limit of the melting point is above 50°C.

[0092] Specific examples of (d) components include, for instance, oxalic acid, malonic acid, α-ketoglutaric acid (2-oxoglutaric acid), 2,2'-thiodiethanolic acid, glycolic acid, 2-oxo-1,3-propanedisulfonic acid, benzene disulfonic acid, naphthalene disulfonic acid, 3-phosphonopropionic acid, and 4-phosphonobutyric acid. From the viewpoint of readily obtaining excellent flux activity and readily achieving the effects of the present invention, oxalic acid, malonic acid, α-ketoglutaric acid, 2,2'-thiodiethanolic acid, and glycolic acid are preferred, with α-ketoglutaric acid being particularly preferred. These can be used alone or in combination of two or more.

[0093] Regarding the content of component (d), based on the total solid content of the semiconductor adhesive, it is preferably 0.1% by mass or more. Furthermore, regarding the content of component (d), based on the total solid content of the semiconductor adhesive, it is preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 2% by mass or less. Regarding the content of component (d), from the viewpoint of connection reliability and reflow resistance during semiconductor device manufacturing, based on the total solid content of the semiconductor adhesive, it is preferably 0.1 to 10% by mass, more preferably 0.1 to 5% by mass, and even more preferably 0.1 to 2% by mass. Additionally, when the organic acid conforms to components (a) to (c), this compound also conforms to component (d), and the content of component (d) is calculated.

[0094] In this embodiment, the equivalent ratio (acidic functional group / basic functional group, molar ratio) of the acidic functional groups in the total amount of component (d) to the basic functional groups in the total amount of component (c) is preferably 1.0 or more, and preferably 3.0 or less. Regarding the above equivalent ratio, it is more preferably 1.3 or more, further preferably 1.5 or more, more preferably 2.5 or less, and even more preferably 2.0 or less.

[0095] (e) Packing

[0096] Depending on the requirements, the semiconductor adhesive of this embodiment may also contain filler (component (e)). Through component (e), the viscosity of the semiconductor adhesive and the physical properties of the cured semiconductor adhesive can be controlled. Specifically, depending on component (e), for example, it is possible to suppress voids generated during bonding and reduce the moisture absorption rate of the cured semiconductor adhesive.

[0097] As component (e), insulating inorganic fillers, whiskers, resin fillers, etc., can be used. Furthermore, as component (e), one type can be used alone, or two or more types can be used simultaneously.

[0098] Examples of insulating inorganic fillers include glass, silica, alumina, titanium dioxide, carbon black, mica, and boron nitride. Silica, alumina, titanium dioxide, and boron nitride are preferred, and silica, alumina, and boron nitride are more preferred.

[0099] Examples of whiskers include aluminum borate, aluminum titanate, zinc oxide, calcium silicate, magnesium sulfate, and boron nitride.

[0100] Examples of resin fillers include fillers made of resins such as polyurethane and polyimide.

[0101] Compared to organic components (such as epoxy resin and curing agents), resin fillers have a lower coefficient of thermal expansion, resulting in significantly improved bonding reliability. Furthermore, the viscosity of semiconductor adhesives can be easily adjusted using resin fillers. Compared to inorganic fillers, resin fillers offer superior stress mitigation capabilities.

[0102] Compared to resin fillers, inorganic fillers have a lower coefficient of thermal expansion, thus enabling the creation of adhesive compositions with lower coefficients of thermal expansion. Furthermore, most inorganic fillers are general-purpose and their particle size is controlled, which also facilitates viscosity adjustment.

[0103] Resin fillers and inorganic fillers each have their own advantages, so either one can be used depending on the application, or they can be used in combination to bring out the functions of both.

[0104] (e) There are no particular restrictions on the shape, particle size, and content of component (e). Furthermore, the physical properties of component (e) can be appropriately adjusted through surface treatment.

[0105] Regarding the content of component (e), based on the total solid content of the adhesive for semiconductors, it is preferably 10% by mass or more, more preferably 15% by mass or more, preferably 80% by mass or less, and more preferably 60% by mass or less. Regarding the content of component (e), based on the total solid content of the adhesive for semiconductors, it is preferably 10 to 80% by mass, more preferably 15 to 60% by mass.

[0106] (e) is preferably composed of an insulating material. If (e) is composed of an insulating material, it is easier to suppress the reduction in insulation reliability (especially HAST resistance) compared to the case where it is composed of a conductive material (e.g., solder, gold, silver, copper, etc.).

[0107] (Other ingredients)

[0108] In the semiconductor adhesive of this embodiment, additives such as antioxidants, silane coupling agents, titanium coupling agents, leveling agents, and ion trapping agents may also be incorporated. These can be used individually or in combination of two or more. The dosage of these additives can be adjusted appropriately to achieve the desired effect.

[0109] The semiconductor adhesive of this embodiment can be in film form. This improves workability when sealing gaps between a semiconductor chip and a wiring substrate, or gaps between multiple semiconductor chips, using a pre-applied method. An example of a method for manufacturing the semiconductor adhesive (film adhesive) of this embodiment, formed into a film, is shown below.

[0110] First, components (a), (b), (c), and (d), and component (e) as needed, are added to an organic solvent. The resin varnish is then dissolved or dispersed through stirring, mixing, and kneading. Next, the resin varnish is applied to a substrate film that has undergone a demolding treatment using a blade coater, roller coater, or applicator. The organic solvent is then removed by heating, forming a film-like adhesive on the substrate film.

[0111] There are no particular limitations on the thickness of the film adhesive. For example, it is preferably 0.5 to 1.5 times the height of the bump before connection, more preferably 0.6 to 1.3 times, and even more preferably 0.7 to 1.2 times.

[0112] If the thickness of the film adhesive is 0.5 times or more of the bump height, the generation of voids caused by unfilled adhesive can be effectively suppressed, further improving connection reliability. Furthermore, if the thickness is 1.5 times or less, the amount of adhesive squeezed out from the chip connection area during connection can be effectively suppressed, thus effectively preventing adhesive from adhering to unnecessary parts. When the thickness of the film adhesive is greater than 1.5 times, the bump has to expel a large amount of adhesive, which can easily lead to poor conductivity. Moreover, compared to the weakening of bumps based on narrow pitch and multiple pins (miniaturization of bump diameter), the expulsion of excess resin will cause greater damage to the bump, therefore it is not preferred.

[0113] If the height of the bump is generally 5 to 100 μm, the thickness of the film adhesive is preferably 2.5 to 150 μm, more preferably 3.5 to 120 μm.

[0114] The organic solvents used in the preparation of resin varnishes preferably possess the property of uniformly dissolving or dispersing the various components. Examples include dimethylformamide, dimethylacetamide, N-methyl-2-pyrrolidone, dimethyl sulfoxide, diethylene glycol dimethyl ether, toluene, benzene, xylene, methyl ethyl ketone, tetrahydrofuran, ethacryloylthion, ethacryloyl acetate, butacryloylthion, dioxane, cyclohexanone, and ethyl acetate. These organic solvents can be used alone or in combination of two or more. The stirring, mixing, and kneading during the preparation of resin varnishes can be carried out using, for example, a mixer, a grinder, a three-roll mill, a ball mill, a bead mill, or a high-speed disperser.

[0115] As a substrate film, there are no particular limitations as long as it has heat resistance capable of withstanding the heating conditions required to evaporate organic solvents. Examples include polypropylene films, polyolefin films such as polymethylpentene films, polyester films such as polyethylene terephthalate films and polyethylene naphthalate films, polyimide films, and polyetherimide films. The substrate film is not limited to a single-layer film composed of these films, but can also be a multilayer film composed of two or more materials.

[0116] Regarding the drying conditions for evaporating the organic solvent from the resin varnish coated on the substrate film, it is preferable to allow the organic solvent to evaporate sufficiently. Specifically, heating at 50 to 200°C for 0.1 to 90 minutes is preferred. The organic solvent is preferably removed to less than 1.5% by mass relative to the total amount of the film adhesive.

[0117] Furthermore, the semiconductor adhesive of this embodiment can also be formed directly on the wafer. Specifically, for example, after spin-coating the above-mentioned resin varnish directly onto the wafer to form a film, the organic solvent can be removed, thereby directly forming a layer composed of semiconductor adhesive on the wafer.

[0118] Regarding the minimum melt viscosity of the semiconductor adhesive of this embodiment, from the viewpoint that it is easier to remove voids and obtain better reflow resistance during curing in a pressurized atmosphere, it is preferably 200 to 10000 Pa·s, more preferably 200 to 5000 Pa·s. The minimum melt viscosity can be measured by the method described in the examples. Regarding the temperature (melting temperature) at which the minimum melt viscosity of the semiconductor adhesive is expressed, it is preferably 100 to 250°C, more preferably 120 to 230°C, and even more preferably 140 to 200°C.

[0119] Regarding the semiconductor adhesive of this embodiment, from the viewpoint of facilitating temporary fixation of semiconductor chips in a temperature range of 60 to 170°C, a melt viscosity of 2000 to 30000 Pa·s at 80°C is preferred, a melt viscosity of 400 to 20000 Pa·s at 130°C is preferred, and a melt viscosity of 4000 to 20000 Pa·s at 80°C and 400 to 5000 Pa·s at 130°C is more preferred. The above melt viscosity can be measured using the methods described in the examples.

[0120] The semiconductor adhesive described above is preferably used in processes where curing occurs through heating under atmospheric or pressurized atmosphere. It is particularly preferred for processes where multiple semiconductor chips are mounted onto a mounting component (semiconductor chip, semiconductor wafer, wiring circuit board, etc.) and temporarily fixed using the semiconductor adhesive, followed by a single curing and sealing under atmospheric or pressurized conditions. When the semiconductor adhesive of this embodiment is used in this process, voids within the adhesive are easily removed under atmospheric or pressurized conditions, resulting in superior resistance to reflow soldering.

[0121] Semiconductor Devices

[0122] The semiconductor device of this embodiment is a semiconductor device formed by electrically connecting the connection portions of a semiconductor chip and a wiring circuit board to each other, or a semiconductor device formed by electrically connecting the connection portions of multiple semiconductor chips to each other. In this semiconductor device, at least a portion of the connection portion is sealed by a cured product of the aforementioned semiconductor adhesive, which is cured by heating under normal or pressurized atmosphere. Hereinafter, reference will be made to... Figure 1 , Figure 2 and Figure 3 The semiconductor device of this embodiment will be described. Figure 1 , Figure 2 and Figure 3 These are cross-sectional views illustrating one embodiment of a semiconductor device that can be manufactured by the method described later.

[0123] Figure 1 This is a schematic cross-sectional view showing the COB-type connection method of semiconductor chips and substrates. Figure 1 The semiconductor device 100 shown includes a semiconductor chip 1 and a substrate 2 (wiring circuit substrate), and an adhesive layer 40 between them. In the case of the semiconductor device 100, the semiconductor chip 1 includes: a semiconductor chip body 10; wiring or bumps 15 disposed on the surface of the semiconductor chip body 10 on the substrate 2 side; and solder 30 disposed on the wiring or bumps 15 as connecting portions. The substrate 2 includes: a substrate body 20; and wiring or bumps 16 disposed on the surface of the substrate body 20 on the semiconductor chip 1 side as connecting portions. The solder 30 of the semiconductor chip 1 is electrically connected to the wiring or bumps 16 of the substrate 2 via metal bonding. The semiconductor chip 1 and the substrate 2 are flip-chip connected via the wiring or bumps 16 and the solder 30. The wiring or bumps 15, 16 and the solder 30 are sealed by the adhesive layer 40, thereby isolating them from the external environment.

[0124] Figure 2 This indicates the COC (Coefficient of Conformity) interconnection method between semiconductor chips. (About...) Figure 2The structure of the semiconductor device 300 shown is the same as that of the semiconductor device 100, except that the two semiconductor chips 1 are connected by flip-chip via wiring or bumps 15 and solder 30.

[0125] exist Figure 1 and Figure 2 In the process, the connecting parts such as wiring or bump 15 can be a metal film called a pad (e.g., gold-plated) or a pillar electrode (e.g., a copper pillar).

[0126] There are no particular restrictions on the semiconductor chip body 10, and various semiconductors can be used, such as elemental semiconductors composed of elements of the same kind, such as silicon and germanium, and compound semiconductors such as gallium arsenide and indium phosphide.

[0127] As for substrate 2, there are no particular limitations as long as it is a wiring circuit substrate. Circuit substrates with wiring (wiring patterns) can be formed by etching away unwanted parts of the metal layer formed on the surface of an insulating substrate whose main components are glass epoxy, polyimide, polyester, ceramic, epoxy, bismaleimide triazine, etc.; circuit substrates with wiring (wiring patterns) formed on the surface of the aforementioned insulating substrate by metal electroplating, etc.; and circuit substrates with wiring (wiring patterns) formed by printing conductive material on the surface of the aforementioned insulating substrate.

[0128] The materials used for connections such as wiring or bump 15 and wiring or bump 16, solder 30, etc., as main components include gold, silver, copper, solder (with main components such as tin-silver, tin-lead, tin-bismuth, tin-copper, tin-silver-copper), tin, nickel, etc., and can be composed of a single component or multiple components. The connections can also have a structure formed by stacking these metals. Among metal materials, copper and solder are relatively inexpensive and therefore preferred. From the viewpoint of improving connection reliability and suppressing warping, the connections may also contain solder.

[0129] As the material for the pad, gold, silver, copper, solder (with main components such as tin-silver, tin-lead, tin-bismuth, tin-copper, tin-silver-copper), tin, nickel, etc., are used as the main components. The pad can consist of a single component or multiple components. The pad can also have a structure formed by stacking these metals. From the viewpoint of connection reliability, the pad may also contain gold or solder.

[0130] On the surface of the wiring or bumps 15, 16 (wiring patterns), a metal layer may also be formed, primarily composed of gold, silver, copper, solder (main components such as tin-silver, tin-lead, tin-bismuth, tin-copper), tin, nickel, etc. This metal layer may consist of a single component or multiple components. The metal layer may also have a structure composed of multiple stacked metal layers. The metal layer may also contain relatively inexpensive copper or solder. From the viewpoint of improving connection reliability and suppressing warping, the metal layer may also contain solder.

[0131] Can be stacked as Figure 1 or Figure 2 The semiconductor device (package) shown is electrically connected using gold, silver, copper, solder (primarily composed of tin-silver, tin-lead, tin-bismuth, tin-copper, tin-silver-copper), tin, nickel, etc. The metal used for connection can also be relatively inexpensive copper or solder. For example, as seen in TSV technology, flip-chip bonding or stacking can be performed by having an adhesive layer between semiconductor chips, forming through-holes in the semiconductor chips for connection to electrodes on the patterned surface.

[0132] Figure 3 This is a schematic cross-sectional view illustrating another embodiment of a semiconductor device (a semiconductor chip stack-up (TSV) method). Figure 3 In the semiconductor device 500 shown, the semiconductor chip 1 and the interposer 5 are flip-chip connected by solder 30 to the semiconductor chip 1 via wiring or bumps 15 formed on the interposer body 50, which serves as a substrate. An adhesive layer 40 exists between the semiconductor chip 1 and the interposer 5. On the surface of the semiconductor chip 1 opposite to the interposer 5, the semiconductor chip 1 is repeatedly stacked with wiring or bumps 15, solder 30, and adhesive layer 40 in between. The wiring or bumps 15 on the patterned surfaces of the front and back sides of the semiconductor chip 1 are connected to each other by through electrodes 34 filling holes that penetrate the interior of the semiconductor chip body 10. Copper, aluminum, or the like can be used as the material for the through electrodes 34.

[0133] This TSV technology also enables signal acquisition from the back side of semiconductor chips that are not normally used. Furthermore, since the through electrode 34 passes vertically through the semiconductor chip 1, the distance between opposing semiconductor chips 1 and between the semiconductor chip 1 and the interposer layer 5 can be shortened, allowing for flexible connections. In this TSV technology, the adhesive layer can be used as a sealing material between opposing semiconductor chips 1 and between the semiconductor chip 1 and the interposer layer 5.

[0134] <Methods for Manufacturing Semiconductor Devices>

[0135] One embodiment of a method for manufacturing a semiconductor device includes: a lamination process in which a first component having a connection portion and a second component having a connection portion are laminated together via a semiconductor adhesive, with the connection portions of the first component and the second component facing each other; and a sealing process in which the semiconductor adhesive is cured by heating under normal pressure or a pressurized atmosphere, and at least a portion of the connection portion is sealed by the cured semiconductor adhesive. The first component is, for example, a wiring circuit board, a semiconductor chip, or a semiconductor wafer, and the second component is a semiconductor chip. In the sealing process, the opposing connection portions are electrically connected to each other by heating the laminate obtained in the lamination process to a temperature above the melting point of the opposing connection portions under normal pressure or a pressurized atmosphere.

[0136] When the first component is a semiconductor chip, the lamination process includes, for example, a process of arranging multiple semiconductor chips on a worktable; and a temporary fixing process of heating the worktable and sequentially arranging other semiconductor chips on each of the multiple semiconductor chips arranged on the worktable using a semiconductor adhesive to obtain a laminate (temporary fixation body) formed by sequentially laminating multiple semiconductor chips, semiconductor adhesive and other semiconductor chips.

[0137] When the first component is a wiring circuit board or a semiconductor wafer, the lamination process includes, for example, a process of placing the wiring circuit board or semiconductor wafer on a worktable; and a temporary fixing process of heating the worktable and sequentially placing a plurality of semiconductor chips on the wiring circuit board or semiconductor wafer placed on the worktable using a semiconductor adhesive, thereby obtaining a laminate (temporary fixation body) formed by sequentially laminating the wiring circuit board, the semiconductor adhesive and the plurality of semiconductor chips, or a laminate (temporary fixation body) formed by sequentially laminating the semiconductor wafer, the semiconductor adhesive and the plurality of semiconductor chips.

[0138] In the temporary fixing process, for example, firstly, a semiconductor adhesive (e.g., a film-like semiconductor adhesive) is applied to a first component or a second component. Then, a semiconductor chip monolithically mounted on a cutting tape is picked up and adsorbed onto a crimping tool (crimping head) of a crimping machine, temporarily fixing it to a wiring circuit board, other semiconductor chips, or semiconductor wafers.

[0139] There are no particular limitations on the method for preparing semiconductor adhesives. For example, when the semiconductor adhesive is in film form, it can be prepared by methods such as heat pressing, roll lamination, or vacuum lamination. The area and thickness of the prepared semiconductor adhesive are appropriately set according to the dimensions of the first and second components, the height of the connecting portion (bump), etc. The semiconductor adhesive can be applied to a semiconductor chip, or the semiconductor wafer with the semiconductor adhesive applied can be diced and monolithically assembled into a semiconductor chip.

[0140] In the temporary fixing process, alignment is required to electrically connect the connecting parts. Therefore, crimping machines such as flip-chip connectors are generally used.

[0141] When a crimping tool picks up a semiconductor chip for temporary fixation, it is preferable that the crimping tool be at a low temperature to prevent thermal transfer of the semiconductor adhesive or similar material onto the semiconductor chip. On the other hand, it is preferable that the semiconductor chip be heated to a high temperature during crimping (temporary crimping) to improve the flowability of the semiconductor adhesive and effectively eliminate entanglement voids. Heating below the starting temperature of the curing reaction of the semiconductor adhesive is preferred. To shorten cooling time, the temperature difference between the crimping tool when picking up the semiconductor chip and the temperature of the crimping tool during temporary fixation is preferably small. This temperature difference is preferably below 100°C, more preferably below 60°C, and even more preferably substantially 0°C. If the temperature difference is above 100°C, the cooling of the crimping tool takes longer, thus tending to reduce productivity. The starting temperature of the curing reaction of the semiconductor adhesive refers to the initial temperature measured using a DSC (manufactured by PerkinElmer Co., Ltd., DSC-Pyirs1) under conditions of a sample volume of 10 mg, a heating rate of 10°C / min, and an air or nitrogen atmosphere.

[0142] The load applied for temporary fixation is appropriately set considering the number of connecting parts (protrusions), the absorption of height deviations of connecting parts (protrusions), and the amount of deformation of connecting parts (protrusions). In the temporary fixation process, it is preferable that the opposing connecting parts contact each other after crimping (temporary crimping). If the connecting parts contact each other after crimping, it is easier to form a metal bond in the connecting parts during the crimping (formal crimping) in the sealing process, and there is a tendency for less penetration of the semiconductor adhesive. In order to eliminate gaps and ensure contact between the connecting parts, a large load is preferred; for example, each connecting part (e.g., protrusion) is preferably 0.0001N to 0.2N, more preferably 0.009N to 0.2N, and even more preferably 0.001N to 0.1N.

[0143] From the perspective of improving productivity, the shorter the pressing time for temporary fixed processes, the better. For example, it can be less than 5 seconds, less than 3 seconds, or less than 2 seconds.

[0144] The heating temperature of the worktable is lower than the melting points of the connecting parts of the first and second components, typically 60 to 155°C, 65 to 120°C, or 70 to 100°C. Heating at this temperature effectively eliminates voids trapped in the semiconductor adhesive. Furthermore, the heating temperature of the worktable is not actually applied to the adhesive itself.

[0145] Regarding the temperature of the crimping tool during temporary fixing, as mentioned above, it is preferable to set it in a manner that minimizes the temperature difference with that of the crimping tool when picking up the semiconductor chip, for example, it can be 80 to 350°C or 100 to 170°C.

[0146] When the lamination process includes the aforementioned temporary fixing process, in the sealing process following the temporary fixing process, the semiconductor adhesive in multiple laminates or laminates containing multiple semiconductor chips can be cured simultaneously or in stages to seal multiple connections simultaneously or in stages. In the sealing process, opposing connections are joined by metal bonding, and the gaps between connections are generally filled by semiconductor adhesive. The sealing process is performed using a device capable of heating the metal of the connections to above the melting point and applying pressure. Examples of such devices include a pressure reflow oven and a pressure oven.

[0147] Regarding the heating temperature (connection temperature) of the sealing process, it is preferable to heat the opposing connection parts (e.g., bump-bump, bump-pad, bump-wiring) at a temperature above the melting point of at least one metal. For example, when the metal of the connection part is solder, it is preferable to heat between 200°C and 450°C. If the heating temperature is too low, the metal of the connection part will not melt, and sufficient metal bonding may not be formed. If the heating temperature is too high, the effect of void suppression will be relatively small, or the solder will tend to scatter easily.

[0148] If a crimping machine is used to apply pressure to the joint, the heat from the crimping machine is difficult to transfer to the semiconductor adhesive (rounded corners) protruding from the side of the joint. Therefore, after crimping (formal crimping), a further heat treatment is usually required to fully cure the semiconductor adhesive. Therefore, it is preferable to apply pressure in the sealing process using air pressure in a pressure reflow oven, pressure oven, or similar equipment, without using a crimping machine. Pressure-based crimping allows for overall heating, shortening or eliminating the heat treatment after crimping (formal crimping), thereby increasing productivity. Furthermore, pressure-based crimping facilitates the simultaneous formal crimping of multiple laminates (temporary fixtures) or laminates with multiple semiconductor chips temporarily fixed. Moreover, from the viewpoint of rounded corner suppression, pressure-based crimping is preferred over direct crimping using a crimping machine. Rounded corner suppression is crucial for the miniaturization and high-density development of semiconductor devices.

[0149] There are no particular restrictions on the atmosphere used for pressing in the sealing process, but an atmosphere containing air, nitrogen, formic acid, etc., is preferred.

[0150] The pressure applied during the sealing process is appropriately set according to the size and number of the components being connected. The pressure can be, for example, above atmospheric pressure but below 1 MPa. From the viewpoint of reducing voids and improving connectivity, a higher pressure is preferred; from the viewpoint of reducing rounded corners, a lower pressure is preferred. Therefore, a pressure of 0.05 to 0.5 MPa is more preferable.

[0151] The crimping time varies depending on the metal composition of the connection, but from the viewpoint of improving productivity, a shorter time is preferred. When the connection is a solder bump, the crimping time is preferably 20 seconds or less, more preferably 10 seconds or less, and even more preferably 5 seconds or less. In the case of copper-copper or copper-gold metal connections, the crimping time is preferably 60 seconds or less.

[0152] Similar to TSV-structured semiconductor devices, when multiple semiconductor chips are stacked three-dimensionally, they can be stacked one by one to form a temporary fixed state, and then the stacked semiconductor chips can be heated and pressurized together to obtain a semiconductor device.

[0153] Example

[0154] The present invention will now be described in more detail with reference to embodiments, but the present invention is not limited to the embodiments.

[0155] The compounds used in the various examples and comparative examples are as follows.

[0156] (a) Composition: thermoplastic resin

[0157] • Phenoxy resin (manufactured by NIPPON STEEL & SUMIKIN CHEMICAL CO.,LTD., trade name "FX293", Tg: approx. 160°C, Mw: approx. 40000)

[0158] • Polyurethane (manufactured by DIC Covestro Polymer Ltd., trade name "T-8175N", Tg: -23℃, Mw: 120000)

[0159] (b) Composition: Thermosetting resin

[0160] • A multifunctional solid epoxy resin with a triphenol methane backbone (manufactured by Mitsubishi Chemical Corporation, trade name "EP1032H60")

[0161] • Bisphenol F type liquid epoxy resin (manufactured by Mitsubishi Chemical Corporation, trade name "YL983U")

[0162] • Liquid epoxy resin X (manufactured by Mitsubishi Chemical Corporation, trade name "YX")

[0163] (c) Ingredients: Curing agent

[0164] ·2,4-Diamino-6-[2'-methylimidazolyl-(1')]-ethyl-triazine isocyanate adduct (manufactured by SHIKOKU CHEMICALS CORPORATION, trade name "2MAOK-PW", Mw: 384)

[0165] (d) Ingredients: Organic acids

[0166] · Glutaric acid (manufactured by FUJIFILM Wako Pure Chemical Corporation, melting point: 98°C, Mw: 132)

[0167] Diglycolic acid (manufactured by Tokyo Chemical Industry Co., Ltd., melting point: 144℃, Mw: 134)

[0168] ·2,2'-Thiodiglycolic acid (manufactured by Tokyo Chemical Industry Co., Ltd., melting point: 131℃, Mw: 150)

[0169] • α-Ketoglutaric acid (manufactured by FUJIFILM Wako Pure Chemical Corporation, melting point: 118°C, Mw: 146)

[0170] • Diphenylhydroxyacetic acid (manufactured by FUJIFILM Wako Pure Chemical Corporation, melting point: 152°C, Mw: 228)

[0171] (e) Packing

[0172] • Methacrylic acid surface-treated silica filler (manufactured by Admatechs Corporation, trade name "180nm SM-EH1", average particle size approximately 180nm)

[0173] • Silica filler (manufactured by Admatechs Corporation, trade name "SE2030", average particle size 0.5μm)

[0174] • Epoxy silane surface-treated silica filler (manufactured by Admatechs Corporation, trade name "SE2030-SEJ", average particle size 0.5μm)

[0175] • Surface-treated silica filler with methacrylic acid (manufactured by Admatechs Corporation, trade name "YA050C-SM1", average particle size approximately 0.05 μm)

[0176] (a) The weight-average molecular weight (Mw) of the components was determined by GPC. The details of the GPC method are as follows.

[0177] Apparatus Name: HPLC-8020 (Product Name, Manufactured by TOSOH CORPORATION)

[0178] Column: 2pieces of GMHXL+1piece of G-2000XL

[0179] Detector: RI detector

[0180] Column temperature: 35℃

[0181] Flow rate: 1 mL / min

[0182] Standard material: polystyrene

[0183] <Fabrication of Adhesives for Film Semiconductors>

[0184] The thermoplastic resin, thermosetting resin, curing agent, organic acid, and filler, in the proportions shown in Table 1 (unit: parts by mass), were added to the organic solvent (cyclohexanone) at a 50% NV value ([mass of the dried coating] / [mass of the coating before drying] × 100). Then, 1.0 mm and 2.0 mm zirconia beads of the same mass as the solid components (thermoplastic resin, thermosetting resin, curing agent, organic acid, and filler) were added to the same container and stirred for 30 minutes using a ball mill (Fritsch Japan Co., Ltd., planetary micro-mill P-7). After stirring, the zirconia beads were removed by filtration, resulting in a coating varnish.

[0185] Using a small precision coating apparatus (manufactured by Yasui Seiki Inc.), the obtained coating varnish was applied to a substrate film (manufactured by Teijin Dupont Film Japan Limited, trade name "purex A55"), and dried in a cleaning oven (manufactured by ESPEC CORP.) (100°C / 10 minutes) to obtain a film-like adhesive with a thickness of 20 μm.

[0186] The following describes the evaluation method for the film adhesives obtained in the examples and comparative examples. The evaluation results are shown in Tables 1 and 2.

[0187] <DSC Measurement>

[0188] The obtained film-like adhesive was weighed in a 10 mg sample onto an aluminum tray (manufactured by Epolead Service Inc.), covered with an aluminum cap, and the evaluation sample was sealed inside the tray using a presser. Measurements were performed using a differential scanning calorimeter (Thermo plus DSC8235E, manufactured by Rigaku Corporation) under a nitrogen atmosphere, at a heating rate of 10 °C / min, and within a measurement temperature range of 30 to 300 °C. As the analytical method for initial temperature, the total area (JIS method) was used. The initial temperature (unit: °C) was determined by calculating the intersection of the baseline of the peak and the point of maximum slope in each DSC curve during analytical indication within a temperature range of 60 to 250 °C. Similarly, as the analytical method for calorific value, the total area (JIS method) was used. The calorific value (unit: J / g) was calculated by integrating the peaks in each DSC curve during analytical indication within a temperature range of 60 to 250 °C.

[0189] <High Temperature Stability Evaluation>

[0190] The film adhesive (initial sample) obtained in the examples and comparative examples was placed in an oven set at 50°C for 3 hours and then placed in an oven set at 70°C. The sample that had undergone 3 hours of heat treatment was then taken out, and the heat-treated evaluation sample A was obtained.

[0191] Using evaluation sample A, following the same procedure as before heat treatment, a differential scanning calorimeter (Thermo plus DSC8235E, manufactured by Rigaku Corporation) was used to calculate the calorific value (in J / g) from 60 to 250°C. This value was then used as the calorific value after heat treatment.

[0192] The reaction rate was calculated using the two obtained calorific values ​​(calorific value of the initial sample and calorific value of evaluation sample A) and the following formula.

[0193] Reaction rate (%) = (Initial calorific value - Calorific value after heat treatment) / Initial calorific value × 100

[0194] <Gap Evaluation>

[0195] (Fabrication of the laminated body C after temporary compression (temporary fixing body C))

[0196] Using a benchtop laminator (product name: Hotdog GK-13DX, manufactured by LAMI CORPORATION INC.), the film adhesive (initial sample) obtained in the above examples and comparative examples was made into a film with a thickness of 40 μm, then cut into 7.5 mm square dimensions, and attached at 80°C to multiple semiconductor chips with solder bumps (chip size: 7.3 mm × 7.3 mm, thickness 0.1 mm, bump (connection) height: approximately 45 μm (total of copper pillars and solder), number of bumps: 1048 pins, spacing 80 μm, product name: WALTS-TEG CC80, manufactured by WALTS CO.,LTD.). By using a flip-chip bonder (FCB3, manufactured by Panasonic Corporation) for heating and pressurization, semiconductor chips with film-like adhesive were sequentially pressed onto other semiconductor chips (chip size: 10mm × 10mm, thickness: 0.1mm, bump count: 1048 pins, pitch: 80μm, product name: WALTS-TEG IP80, manufactured by WALTSCO.,LTD.) for temporary fixation, resulting in a temporarily pressed laminate C (temporary fixation body C). The pressing conditions were set to 130℃, 75N, and 3 seconds.

[0197] The temporarily pressed laminate (temporary fixation body C) was placed in an oven set at 80°C and heated for 6 hours. The sample was then removed, and the temporarily pressed laminate (temporary fixation body D) after 80°C heat treatment was obtained.

[0198] The temporarily pressed laminate D (temporary fixture D) was placed in an oven of a pressurized oven apparatus (manufactured by NTT Advanced Technology Corporation). The pressure inside the oven was set to 0.8 MPa, and the temperature was increased from room temperature to 190°C at a rate of 20°C / min. Then, the pressure and temperature were maintained, and the laminate was heated under pressurized atmosphere for 1 hour to obtain the evaluation installation sample E.

[0199] (Analysis and Evaluation)

[0200] The appearance images of the above-mentioned evaluation installation samples were captured using an ultrasonic imaging diagnostic device (product name: Insight-300, manufactured by Insight CO.,LTD.).

[0201] [Measurement Conditions]

[0202] Probe frequency: 180MHz

[0203] Diagnostic mode: Echo (pulse-reflex method)

[0204] Images of the adhesive layer between the chips were read using a scanner (GT-9300UF, manufactured by Seiko Epson Corporation). Image processing software (Adobe Photoshop) was used to identify voids in the read images through tone correction and secondary classification, and the proportion of voids was calculated using histograms. The total area of ​​the adhesive layer including voids was set to 100%. Cases with a void area proportion less than 10% were designated as "A", cases with a void area proportion greater than 10% but less than 30% were designated as "B", and cases with a void area proportion greater than 30% were designated as "C". The evaluation results are shown in Table 1.

[0205] <Crack Confirmation at Connection Point>

[0206] (Fabrication of the laminated body F after temporary compression (temporary fixing body F))

[0207] Using a benchtop laminator (product name: Hotdog GK-13DX, manufactured by LAMI CORPORATION INC.), the film adhesive (initial sample) obtained in the above examples and comparative examples was made into a film with a thickness of 40 μm, then cut into 7.5 mm square dimensions, and attached at 80°C to multiple semiconductor chips with solder bumps (chip size: 7.3 mm × 7.3 mm, thickness 0.1 mm, bump (connection) height: approximately 45 μm (total of copper pillars and solder), number of bumps: 1048 pins, spacing 80 μm, product name: WALTS-TEG CC80, manufactured by WALTS CO.,LTD.). By using a flip-chip bonder (FCB3, manufactured by Panasonic Corporation) for heating and pressurization, semiconductor chips with film-like adhesive were sequentially pressed onto other semiconductor chips (chip size: 10mm × 10mm, thickness: 0.1mm, bump count: 1048 pins, pitch: 80μm, product name: WALTS-TEG IP80, manufactured by WALTSCO.,LTD.) for temporary fixation, resulting in a temporarily pressed laminate F (temporary fixation body F). Regarding the pressing conditions, heat was applied in stages at 190℃ / 25N / 10 seconds, 260℃ / 25N / 20 seconds, and 100℃ / 25N / 5 seconds (set heating time for each temperature increase: 0.1 seconds), and pressing was performed.

[0208] The temporarily pressed laminate F (temporary fixture F) was placed in an oven of a pressurized oven apparatus (manufactured by NTT Advanced Technology Corporation). The pressure inside the oven was set to 0.8 MPa, and the temperature was increased from room temperature to 190°C at a rate of 20°C / min. Then, the pressure and temperature were maintained, and the laminate was heated under pressurized atmosphere for 1 hour to obtain the evaluation installation sample G.

[0209] Regarding the aforementioned evaluation samples, a benchtop polisher (Refine Polisher, manufactured by Refine Tec Ltd.) was used to polish until the bump connections inside the chip were exposed. Water-resistant polishing paper was initially used with a size of 200 cm Φ and a grit of 1000, then changed to a grit of 2000, polishing continued until the connections were exposed. Further polishing was then performed using alumina solution (suspension solution) A-0.3 microns (manufactured by Refine Tec Ltd.). The exposed bump connections were observed using a SEM (TM3030Plus benchtop microscope, manufactured by Hitachi High-Tech Corporation) to confirm the presence or absence of cracks within the solder and at the solder-Cu interface.

[0210] <Evaluation of Connectivity>

[0211] The evaluation of the installed sample G was conducted using a circuit testing machine (POCKET TESTER4300COUNT, CUSTOM), and the connectivity was evaluated by measuring the resistance value of the chip's inner periphery. The circuit diagram of the chip used for installation (chip size: 7.3mm × 7.3mm, thickness 0.1mm, bump (connection) height: approximately 45μm (total of copper pillars and solder), number of bumps: 1048 pins, pitch 80μm, product name: WALTS-TEG CC80, manufactured by WALTS CO.,LTD.) is shown below. Figure 4 In this circuit, the resistance between terminals a and b in the diagram is the resistance of the chip's inner periphery. If this resistance is less than 35Ω, the connection is good; if it is greater than 35Ω or the resistance cannot be measured, the connection is poor.

[0212] <Evaluation of solder wettability>

[0213] Regarding the above evaluation, the installed samples were used to observe the cross-section of the connection using SEM in the same manner as the confirmation of cracks in the connection. A solder wetting of more than 90% on the Cu wiring was evaluated as "A" (good), and a solder wetting of less than 90% was evaluated as "B" (insufficient wetting).

[0214] [Table 1]

[0215]

[0216] [Table 2]

[0217]

[0218] Symbol Explanation

[0219] 1-Semiconductor chip, 2-Substrate, 10-Semiconductor chip body, 15, 16-Wires or bumps, 20-Substrate body, 30-Solder, 34-Through electrode, 40-Adhesive layer, 50-Intermediate layer body, 100, 300, 500-Semiconductor device.

Claims

1. An adhesive for semiconductors, comprising a thermoplastic resin, a thermosetting resin, a curing agent, an organic acid, and a filler, wherein, The organic acid is a compound having two or more acidic functional groups and an acid dissociation constant pKa of less than 4.

0. The acidic functional group contains at least one group selected from the group consisting of carboxyl, sulfonic acid, and phosphate groups. The curing agent contains amine curing agents or imidazole curing agents. The equivalent ratio of the acidic functional groups contained in the organic acid to the basic functional groups contained in the curing agent is 1.0 or more and 3.0 or less. The content of the thermoplastic resin, based on the total solid content of the semiconductor adhesive, is 1% by mass or more and 30% by mass or less. The content of the thermosetting resin, based on the total solid content of the semiconductor adhesive, is 5% by mass or more and 80% by mass or less. When the curing agent contains the amine curing agent, its content relative to 100 parts by weight of the thermosetting resin is 0.1 parts by weight or more and 10 parts by weight or less. When the curing agent contains the imidazole curing agent, its content relative to 100 parts by weight of the thermosetting resin is more than 0.1 parts by weight and less than 10 parts by weight. The content of the organic acid is 0.1% by mass or more and 10% by mass or less, based on the total solid content of the semiconductor adhesive. The content of the filler is 10% by mass or more and 80% by mass or less, based on the total solid content of the semiconductor adhesive.

2. The adhesive for semiconductors according to claim 1, wherein, The organic acid comprises compounds represented by the following general formulas (1-1), (1-2), or (1-3). In equations (1-1), (1-2), and (1-3), R 1 R represents an electron-withdrawing group. 2 R represents a hydrogen atom or an electron-withdrawing group. 3 Indicates a hydrogen atom or a monovalent organic group, X represents an oxygen atom or a sulfur atom, n 1 n represents an integer from 0 to 15. 2 and n 3 They represent n respectively 2 +n 3 The choice of integers greater than 1, where m represents 1 or 2, is an integer between 2 and 15. Additionally, there are multiple R values. 3 They can be the same as each other, or they can be different.

3. The semiconductor adhesive according to claim 1 or 2, wherein, The organic acid has a melting point of 50 to 250°C.

4. The semiconductor adhesive according to claim 1 or 2, wherein, The curing agent contains amine-based curing agents.

5. The semiconductor adhesive according to claim 1 or 2, wherein, The curing agent contains imidazole-based curing agents.

6. The semiconductor adhesive according to claim 5, wherein, The imidazole curing agent has a structure containing a triazine ring.

7. A method for manufacturing a semiconductor device, wherein, The semiconductor device is a semiconductor device formed by electrically connecting the connection parts of a semiconductor chip and a wiring circuit board, or a semiconductor device formed by electrically connecting the connection parts of multiple semiconductor chips. The method for manufacturing the semiconductor device includes a sealing step of heating the semiconductor adhesive according to any one of claims 1 to 6 under normal or pressurized atmosphere to cure it, and sealing at least a portion of the connection portion with the cured semiconductor adhesive.

8. The method for manufacturing a semiconductor device according to claim 7, further comprising, prior to the sealing process: The process of arranging multiple semiconductor chips on a workbench; as well as The worktable is heated to 60 to 155°C, and other semiconductor chips are sequentially arranged on each of the plurality of semiconductor chips arranged on the worktable via the semiconductor adhesive, thereby obtaining a temporary fixing process for a plurality of laminates formed by sequentially stacking the semiconductor chips, the semiconductor adhesive and the other semiconductor chips.

9. The method for manufacturing a semiconductor device according to claim 7, further comprising, prior to the sealing process: The process of arranging wiring circuit boards or semiconductor wafers on a workbench; as well as The worktable is heated to 60 to 155°C, and multiple semiconductor chips are sequentially arranged on the wiring circuit board or semiconductor wafer disposed on the worktable using the semiconductor adhesive, to obtain a temporary fixing process of a laminate formed by sequentially stacking the wiring circuit board, the semiconductor adhesive and multiple semiconductor chips, or a laminate formed by sequentially stacking the semiconductor wafer, the semiconductor adhesive and multiple semiconductor chips.

10. A semiconductor device comprising a semiconductor chip and a wiring circuit board, wherein the connection portions of the respective semiconductor chips are electrically connected to each other, or a semiconductor device comprising multiple semiconductor chips, wherein the connection portions of the respective semiconductor chips are electrically connected to each other. At least a portion of the connection is sealed with the cured product of the semiconductor adhesive of any one of claims 1 to 6, which is cured by heating under normal or pressurized atmosphere.

Citation Information

Patent Citations

  • Method for bonding semiconductor wafer and method for manufacturing semiconductor device

    JP2008294382A

  • Method for manufacturing semiconductor device, method for manufacturing semiconductor wafer with semiconductor element, method for manufacturing semiconductor wafer with adhesive layer, and method for manufacturing semiconductor wafer laminated body

    WO2012153846A1